Impact of Firm Size and Capital Structure on the Profitability of Nepalese Commercial Banks - Dahal, Joshila; Joshi, Kalpana Kumari; Shakya, Leesa; Joshi, Mahesh (Nepalese Journal of Economics, 2024)
The study examines the impact of firm size and capital structure on the profitability of Nepalese commercial banks. Return on equity and return on assets are selected as the dependent variables. The selected independent variables are debt to equity ratio, debt to assets ratio, capital adequacy ratio, loan to deposits ratio, assets tangibility and firm size. The study is based on secondary data of 13 commercial banks with 104 observations for the period from 2014/15 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of firm size and capital structure on the profitability of Nepalese commercial banks.The study showed that capital adequacy ratio has a positive impact on return on assets. It means that increase in capital adequacy ratio leads to increase in return on assets. Likewise, debt to equity ratio has a negative impact on return on assets and return on equity. It means that increase in debt-to-equity ratio leads to decrease in return on assets and return on equity. Further, this study showed that assets tangibility has a positive impact on return on assets and return on equity. It means that increase in assets tangibility leads to increase in return on assets and return on equity. Moreover, firm size has a positive impact on return on equity. It indicates that increase in firm size leads to increase in return on equity. Similarly, debt to assets ratio has a positive impact on return on equity. It means that increase in debt to assets ratio leads to increase in return on equity.